1971
DOI: 10.1177/000992287101000619
|View full text |Cite
|
Sign up to set email alerts
|

Lung Puncture-Aspiration as a Bacteriologic Diagnostic Procedure in Acute Pneumonias of Infants and Children

Abstract: Lung puncture-aspiration is simple and generally innocuous. For the study of acute pneumonia it is superior to examination of nasopharyngeal, throat or laryngeal cultures and gives more positive results than does blood culture. It can be extremely useful in investigational studies and with selected patients in whom identification of the precise pathogen is necessary for optimal antibiotic therapy. ETIOLOGIC diagnosis of lower respiratory tract infections has always been a vexing problem. Commonly employed diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1973
1973
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 13 publications
(2 reference statements)
0
10
0
1
Order By: Relevance
“…Reliable information on the etiology of pneumonia based on lung tap was also obtained for Latin America (52,110,122,142,149); this method is also used in Africa and Oceania (115,152,180). H. influenzae, supposedly often Hib, turned out to be an essential pathogen in all these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reliable information on the etiology of pneumonia based on lung tap was also obtained for Latin America (52,110,122,142,149); this method is also used in Africa and Oceania (115,152,180). H. influenzae, supposedly often Hib, turned out to be an essential pathogen in all these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the best-known entity, meningitis, all Hib entities such as epiglottitis, nonfocal septicemia, cellulitis, osteomyelitis, and septic arthritis were identified. Hib pneumonia associated with bacteremia was differentiated from pneumonia without bacteremia because several studies from the developing world (3,115,122,152,180,183; S. P. Lupisan, H. Nohynek, M. R. Z. Capeding, L. T. Sombrero, G. Esparar, E. Herva, B. P. Quiambao, P. E. Abucejo, L. G. Pascual, J. Arcay, V. L. Tallo, P. H. Mäkelä, and P. Ruutu, Abstr. Int.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…***Anatomia Patoldgica, Hospital Sotero del Rfo, 4.-Cultivo de muestra obtenida por puncidn pulmonar. (4,6,7,8,9,10). Este metodo es el mas apropiado, por: a) Obtener la muestra en forma directa del foco comprometido (evitandose el riesgo de los falsos positives); b) T6cnica simple; c) Bajo porcentaje de complicaciones (1-2%).…”
Section: -Cultivos De Aspirados Traqueales (Por Laringoscopia O Por Punclassified
“…2 The burden of Hib disease is proved in large studies conducted in Africa, Asia and Latin America where the vaccine was found to be useful in reducing childhood infections. [3][4][5] In view of demonstrated safety and efficacy, World Health Organization (WHO) recommends that conjugate Hib vaccines should be included in all routine infant immunization program. 2 Hib vaccination also reduces nasopharyngeal colonization with the organism, leading to substantial reduction in disease incidence than can be directly attributed to the effects of the vaccine.…”
mentioning
confidence: 99%